Comprehensive cost-of-illness analysis of pressure ulcer treatment: A real-world study at a Czech university hospital - Krupová, Lenka; Pokorná, Andrea; Krupa, Miroslav; Benešová, Klára (International wound journal, 2025)
Pressure ulcers (PUs) impose a significant economic burden on healthcare systems, affecting patient quality of life and leading to substantial treatment costs. This study presents a cost-of-illness analysis of PU treatment in hospitalized patients in the Czech Republic, based on real-world clinical data. The analysis was conducted using a comprehensive methodology at a Czech university hospital, involving 304 hospitalizations. The study included all hospitalized patients with PUs. Data were collected employing a bottom-up, person-based approach, which refers to the collection and analysis of cost data at the individual patient level. This method captures detailed resource utilization for each patient. The methodology accounted for both systemic and local costs, including materials, medications, caregiver time, and procedures. The study involved 304 hospitalizations, with a mean length of stay of 13 days. The total cost of PU treatment, excluding pharmacotherapy, had a median of €678, while including pharmacotherapy, the median cost rose to €929. Younger patients incurred higher treatment costs. Significant cost variations were observed among different departments. We developed and applied a novel cost model to quantify the expenses associated with PUs, which accurately highlighted the financial burden in the hospital care setting. We present a rigorous methodology for PU cost-of-illness analysis, providing a valuable tool for future research and clinical practice. This comprehensive approach supports the development of targeted interventions to reduce the incidence and severity of PUs, ultimately improving patient care and reducing healthcare costs.
Keywords: Pressure Ulcer; Length of Stay; patients; Male; Česká republika; hospitalizace; náklady na zdravotní péči; Adult; Aged; dospělí; Cost of Illness; mužské pohlaví; senioři; délka pobytu; cost analysis; healthcare costs; Czech Republic; senioři nad 80 let; nemocnice univerzitní; lidé; ženské pohlaví; Humans; Health Care Costs; Hospitalization; Aged, 80 and over; Hospitals, University; pressure ulcers; dekubity; Female; treatment costs; lidé středního věku; osobní újma zaviněná nemocí; Middle Aged